Effect of methoxyethyl and methyl ester groups on platelet compatibility of polymers. (September 2018) - Kinoshita, Takuya; Yahata, Chie; Miwa, Yuko; Tsukamoto, Hideo; Mochizuki, Akira
Poly(2-methoxyethyl acrylate) is known to exhibit good blood compatibility. This study was designed to understand the effect of methoxyethyl ester groups on the platelet compatibility of polymers. Polymers bearing either methoxyethyl ester or methyl ester groups, such as poly(acrylate)s, poly(methacrylate)s, and poly(vinyl benzoate)s, were prepared and a comparative study of the ester groups was performed. Polymers bearing methoxyethyl ester groups and poly(methyl acrylate) exhibited good and approximately equal platelet compatibility, regardless of their chemical structure, as estimated using flow cytometry and scanning electron microscopy. To understand these results, the static properties (namely, surface wettability by contact angle and water structure by differential scanning calorimetry) and a dynamic property ( 13 C-NMR relaxation time of the functional groups) were analyzed. The results showed that platelet compatibility could be interpreted from the water structure and dynamic property.